2021
DOI: 10.3390/app11125681
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Potassium Fertilization Improve Rocket Growth without Affecting Tilapia Growth and Histomorphology Characteristics in Aquaponics

Abstract: Aquaponics provides an alternative opportunity for the combined production of fish and plants. Most of the essential nutrients required for optimal plant growth can be supplied from the fish feed, except for K and Fe. These nutrients are usually inadequate in fish feed. In this study, red tilapia and rocket plants were co-cultivated in an aquaponics system along with the extra addition of K and Fe. Fish growth, morpho-anatomical characteristics, and K and Fe loading on fish gills were studied. Plant growth par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 56 publications
2
3
0
4
Order By: Relevance
“…The time point of D12 appears to be crucial in determining the course of chl biosynthesis and degradation in the present experiment's no external input CAP system (SPAD index, Figure 2a). A similar response has been reported for lettuce [11], spinach [20] and rocket [49] grown in analogous systems. Low chlorophyll levels can reduce the LUE, i.e., the efficiency of utilizing absorbed photosynthetically active radiation for biomass production, ultimately resulting in inefficient rates of photosynthesis [50].…”
Section: Discussionsupporting
confidence: 84%
“…The time point of D12 appears to be crucial in determining the course of chl biosynthesis and degradation in the present experiment's no external input CAP system (SPAD index, Figure 2a). A similar response has been reported for lettuce [11], spinach [20] and rocket [49] grown in analogous systems. Low chlorophyll levels can reduce the LUE, i.e., the efficiency of utilizing absorbed photosynthetically active radiation for biomass production, ultimately resulting in inefficient rates of photosynthesis [50].…”
Section: Discussionsupporting
confidence: 84%
“…In our experiment, the HS solution had a higher concentration of nitrate (398.7 mg/L) compared to EVT (265.8 mg/L) and the SVT solution, which had a very low concentration N, P, and K are essential elements with both physiological and structural functions in plants. According to Stathopoulou et al [24], higher concentrations of N, P, K, and Fe are related to enhanced biomass production in rocket plants. Our study also showed that the HS and EVT solutions had higher levels of nitrate, P, K, Ca, Mg, and other micronutrients, leading to increased biomass production compared to the SVT treatment, which had a lesser nutrient concentration.…”
Section: Spad Value Of Diplotaxis Muralismentioning
confidence: 99%
“…A 400-liter fish tank with a cultivation rate of 655 g/m3 and floating pellets containing 47% crude protein as food. Potassium and iron nutrients were added to the water to encourage vegetative development, since these additions had no detrimental impacts on growth, survival rate, or the fish in the experiment [68]. Research has shown that the addition of 3 percent dried Rocket leaves to the feed of Nile tilapia fish subjected to heat stress at 32°C and cold temperatures of 13°C increased the fish's final growth, total and daily weight gain, specific growth, condition factor, and immunity [69].…”
Section: Effect On Growth Metrics and Nutrient Utilizationmentioning
confidence: 99%